Inside the Small Church - Pappas, Anthony G. (Rowman & Littlefield Publishers, 2001)
Even as so-called megachurches capture the attention of many church watchers, small congregations continue to dominate America’s religious landscape in both rural and urban settings. Although sometimes obscured by their larger siblings, these small churches play a prominent role and hold a unique place in both local and national cultures. How can leaders help to keep these often at-risk churches alive and to meet their potential for ministry? Small-church expert Tony Pappas has gathered a cornucopia of essays into an indispensable book for anyone interested in the rich life of these small but significant congregations. Drawing on classic and updated articles by a variety of writers from his own small-church newsletter The Five Stones; from Alban journals Action Information and Congregations; and adding new pieces developed especially for this volume, Pappas provides timeless ideas on learning to value, pastor, develop, and lead the small church. In addition to time-honored articles by the editor, other contributors to this volume include Sherry and Douglas Alan Walrath, Gary Farley, Lawrence W. Farris, Loren Mead, Caroline Westerhoff, Steven Burt, Carl Dudley, David Ray, James Lowery, and a host of others known for their work-and love-for the small church. Readers of Inside the Small Church will come away with a renewed love and appreciation for these vital congregations as well as with new skills for ministry.